The Relationship Between Future Career Orientation and Career Decision Making Self-Efficacy in Final Year Students - Nabila, Aprima Tasya (Universitas Bunda Mulia, 2023)
Confusion and delays in making career decisions after completing higher education in final year students are caused by poor self-confidence in making career decisions. When final year students have a good future orientation, they tend to have a career picture and have career planning, so that after they complete their education they become more confident in making career decisions. This study aims to determine the relationship between future orientation and career decision making self-efficacy in final year students at Andalas University. The research method used in this study is a quantitative method of correlational design with Spearman Rank analysis technique. Respondents of this study amounted to 364 final year students of Andalas University with the sampling method was a proportional sample from each faculty. Data collection in the study used the Prospective Life Course Questionnaire Future and Work (α = .935) measurement tool for future orientation and Career Decision Making Self-Efficacy Scale-Short Form (α = .935) for confidence in making decisions career adapted into Indonesian. The results showed a positive relationship between future orientation and career decision making self-efficacy in final year students of Andalas University. These results can be seen from the results of correlation analysis which shows a correlation coefficient (r) value of .651 with a significance value of .000.